Consumer Perception Towards Dairy Products in India- An Empirical Study - Pallathadka, Laxmi Kirana; Pallathadka, Harikumar; Devi, Mairembam Sangita (Integrated Journal for Research in Arts and Humanities, 2022)
Milk and milk particulars have a significant spot in the healthy routine of mortal brutes because of medical advantages. The request interest exceptionally mandates the event of milk running for dairy particulars. It examined the job of conjoint examination to assure purchasers' responses to an item during idea testing and test promoting and likewise for the differences of being particulars. The assurance of guests' musts and requirements in a productive manner necessitates that associations comprehend the characteristics of their products that the guests generally esteem. Parochial families burn through just about 50 percent of complete milk advancement in India. The leftover 50 percent is sold in the homegrown request. Of the portion of milk sold in the homegrown request, around 50 is devoured in liquid, 35 percent is burned-through as conventional particulars like cheddar and yogurt. The remaining 15 is consumed like a spread, ghee, milk greasepaint, and other managed journal specifics such as kid food types, firmed yogurt, whey greasepaint, casein, and milk-egg whites. According to the Indian Dairy Assiduity Analysis, India is the world's largest milk producer, accounting for roughly 17 percent of global milk production. Our discussion resulted in the collection of written inspections on issues affecting visitors when purchasing milk and the assurance of limitations and guidelines for our future disquisition action. A sample of 121 respondents was collected from respondents through a “standard questionnaire,” which was created on a five-point interval scale.